CONCEPT AND APPLICATION OF AUDIT IN INFORMATION SYSTEMS - Sangkala, Masnawaty (Transpublika Publisher, 2024)
The motivation behind this research lies in the critical role of sophisticated information systems in financial auditing, amidst increasing demands for transparency and accuracy. As these systems integrate into business operations, understanding their effectiveness in mitigating risks and ensuring compliance with GAAP is essential for maintaining financial integrity and stakeholder confidence. This study aims to assess and understand the extent of the effectiveness of the audit application information system in providing accurate and timely information, as well as reducing risks within acceptable limits by the company. An examiner has the principal intention to provide an opinion on the feasibility of financial statements in all significant aspects in accordance with Generally Accepted Accounting Principles (PABU). The point is to ensure that users of financial statements have confidence that the report has been prepared in accordance with established standards, and therefore, evaluation from third parties that are free from related interests is needed. The approach used is a descriptive approach based on quantitative analysis by collecting data from various articles and websites used as references. In application audits, it is also common to check general controls because general controls contribute to the effectiveness of application controls.